KORELASI KARAKTERISTIK DENGAN PENGETAHUAN PERAWAT MENGENAI AUSTRALIAN TRIAGE SCALE - Astika, I Kadek; Sanjana, I Wayan Edi; Widyandari, Ni Made Ayu Sukma (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p11, 2023)
Triage is a very essential aspect of emergency services, especially intrahospital. Triage in its technical implementation is carried out by health workers who first meet patients in the emergency room. Health workers who are in charge of prioritizing patients using triage, must at least contain interpretation of clinical history and physiological assessment to label, and place patients in the appropriate area. Fast and precise triage is the key to successful performance in providing emergency services. Assessing the priority of patients who are inappropriate for their condition has the risk of increasing morbidity rates, affecting the results of care, or outcomes that will be determined. This study aims to determine the correlation between characteristics and knowledge of health workers regarding ATS triage at Wangaya Hospital, Denpasar City. This study is a descriptive correlative study with a cross sectional approach. This research was conducted in the emergency room of Wangaya Hospital, Denpasar City within a period of 1 month in November 2022. The sample in this study amounted to 31 health workers consisting of 24 nurses and 7 doctors. Samples were selected using total sampling technique. Gamma test was used to determine the relationship between the two variables. The results showed that from the characteristics of health workers, only the history of triage training had a statistical relationship with ATS triage knowledge with a p- value of 0,021. There was no statistical association between age, gender, education history, BTCLS training history, PPGD training and length of employment history with ATS triage knowledge. Regular triage training can be carried out with roleplay or video methods to increase health workers' knowledge of ATS triage.